2009
DOI: 10.1038/ejcn.2009.25
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A deficiency and other factors associated with severe tuberculosis in Timor and Rote Islands, East Nusa Tenggara Province, Indonesia

Abstract: Background: Plasma zinc and vitamin A concentrations have been reported to be low in tuberculosis (TB) patients in some studies, although it is not clear whether this constitutes a risk for a more severe clinical presentation among TB patients. The acute phase reaction may also deplete zinc and vitamin A in the plasma. Therefore, we further studied these associations. Methods: We carried out a cross-sectional study among newly diagnosed sputum smear-positive TB patients in East Nusa Tenggara. The patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 18 publications
0
33
0
2
Order By: Relevance
“…Vitamin A deficiency is commonly observed in individuals with prevalent TB and is associated with disease severity, but data from cohort studies evaluating vitamin A deficiency state and risk of downstream TB in high-TB, high-HIV settings are limited 10,19–21 . In vitro studies have demonstrated an ability of vitamin A to inhibit M. tuberculosis replication in culture and within macrophages 64–66 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin A deficiency is commonly observed in individuals with prevalent TB and is associated with disease severity, but data from cohort studies evaluating vitamin A deficiency state and risk of downstream TB in high-TB, high-HIV settings are limited 10,19–21 . In vitro studies have demonstrated an ability of vitamin A to inhibit M. tuberculosis replication in culture and within macrophages 64–66 .…”
Section: Discussionmentioning
confidence: 99%
“…Animal models highlight a plausible role of deficiencies and TB risk and clinical outcomes 17,18 . Further, decreased levels of multiple micronutrients, including vitamins A 19–21 ; carotenoids 22 ; vitamin D 2329 , vitamin E 3032 and selenium 3236 are frequently observed in patients with TB and often correlate with severity of disease. However, previous studies have mostly been cross-sectional, focused on single micronutrients, or supplementation trials including patients with prevalent TB, and most did not adjust other important variables including BMI or inflammatory markers.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of vitamin A deficiency in sputum-positive pulmonary TB patients compared with healthy subjects was confirmed[1,4]. and associated with the future of pulmonary adult TB patients [5]. …”
Section: Introductionmentioning
confidence: 99%
“…The present study is in line with another study conducted in the community of Nusa Tenggara Timur province, stating that low vitamin A intake carries a 3.2-fold risk of pulmonary tuberculosis. (16) On the other hand, a study conducted in Delft, Western Cape, South Africa, found no relationship between vitamin A intake and pulmonary tuberculosis incidence. (18) In the group of cases, 57.9% of the community members had poor adequacy levels for vitamin C, whereas in the group of controls, 26.3% had poor adequacy levels for vitamin C. This shows that in the group of controls the adequacy level for vitamin C was higher than that in the group of cases.…”
Section: Discussionmentioning
confidence: 99%
“…A similar study in the province of Nusa Tenggara Timur found that respondents with poor energy intakes were closely associated with pulmonary tuberculosis incidence. (16) The body uses 60-70% of the total energy requirement for maintaining its basic functions, called the basal metabolism. The energy is required for the basal metabolism and such body functions as digestion, processing, and absorption of food in the digestive tract, moving, walking, working, and other activities.…”
Section: Discussionmentioning
confidence: 99%